Is the Milky Way still breathing?: RAVE-Gaia streaming motions - Carrillo, Ismael; Grebel, Eva K.; Just, Andreas (Arxiv, 2018)
We use data from the Radial Velocity Experiment (RAVE) and the Tycho-Gaia astrometric solution catalogue (TGAS) to compute the velocity fields yielded by the radial (VR), azimuthal (Vphi) and vertical (Vz) components of associated Galactocentric velocity. We search in particular for variation in all three velocity components with distance above and below the disc midplane, as well as how each component of Vz (line-of-sight and tangential velocity projections) modifies the obtained vertical structure. To study the dependence of velocity on proper motion and distance we use two main samples: a RAVE sample including proper motions from the Tycho-2, PPMXL and UCAC4 catalogues, and a RAVE-TGAS sample with inferred distances and proper motions from the TGAS and UCAC5 catalogues. In both samples, we identify asymmetries in VR and Vz. Below the plane we find the largest radial gradient to be dVR / dR = -7.01+- 0.61 km\s kpc, in agreement with recent studies. Above the plane we find a similar gradient with dVR / dR= -9.42+- 1.77 km\s kpc. By comparing our results with previous studies, we find that the structure in Vz is strongly dependent on the adopted proper motions. Using the Galaxia Milky Way model, we demonstrate that distance uncertainties can create artificial wave-like patterns. In contrast to previous suggestions of a breathing mode seen in RAVE data, our results support a combination of bending and breathing modes, likely generated by a combination of external or internal and external mechanisms.